Balanced Human Resource Scorecard towards Quality, Efficiency and Timeliness of Secondary Teachers in Sarangani Province - Cristita P. Garde (PT FORMOSA CENDEKIA GLOBAL, 2023)
The study focused to explore the balanced human resource scorecard towards quality, efficiency and timeliness of Secondary Teachers in Sarangani Province. There were one hundred fifty-seven (157) secondary teachers who served as respondents of the study. They are from the Alabel National High School and Malandag National High School respectively. The ANOVA shows that the teachers’ responses about the difference on the balanced human resource scorecard across Profile Age Group, Sex, Grade Level, Teaching Position and Teaching Experience are not significantly different. Results revealed that teachers have very high level of balanced human resource scorecard. Similarly, teachers have outstanding performance level using the balanced human resource scorecard. On the other hand, no correlation is found between balanced human resource scorecard and the performance level of teachers. Furthermore, no significant difference on the responses of the teachers with regards to balanced human resource scorecard and when grouped according to profile.